Analisis Pengaruh Program Makmur Terhadap Peningkatan Produksi Usahatani Padi - Nabila, Putri; Bakar, Abu; Wijaya, I Putu Eka (Hasanuddin University, 2024)
Rice is the basic food product consumed by every Indonesian citizen. Tempuran and Pedes sub-districts are the areas that contribute to the highest rice production in Karawang Regency. The instability of rice production in Karawang Regency is due to problems such as the narrowing land area due to land conversion, limited use of subsidized fertilizers, and expensive pesticide prices. The Makmur programme is one form of effort to overcome rice production problems. This study aims to analyze the effect of land area, seeds, fertilizers, pesticides, labour, machinery, and the Makmur program dummy on rice production. The research method used in this research is the descriptive quantitative method. The data collection method was carried out by interviewing and observing all participants of the Makmur programme. The data were processed using IBM SPSS 26 and analyzed using the multiple regression analysis method with cobb-douglas production function. The results showed that: the production of all variables had a significant effect, and partially the variables in the regression calculation before the Makmur program, namely the variable labour (lnX5) and machine power (lnX6) had a significant effect on rice production (Y). In the regression calculation after the Makmur program all variables, namely land area, (lnX1), seeds (lnX2), fertilizer (lnX3), pesticides (lnX4), labour (lnX5) and engine power (lnX6), do not have a significant effect on rice paddy production (lnY). In the regression calculation with the Makmur program dummy, namely pesticides (lnX4) and labour (lnX5) have a significant influence on the dependent variable or rice paddy production (lnY).